The Effectiveness Of Spiritual Emotional Freedom Technique (SEFT) On The Decrease of Psychological Issues In Cancer Patients: A Systematic Review - Putri Salsabila, Meliawati; Novieastari, Enie (Media Keperawatan Indonesia, 2024)
Cancer is a cellular disease characterised by disruption or failure of multi-application regulatory mechanisms and other homeostasis functions in multicellular organisms. Basically, cancer can occur due to genetic changes (mutations), especially in the gene that regulates growth, namely oncogenes. Self-concept is a mental representation that a person has of who they are, including self-assessment, body image, self-esteem, and social roles. For women with cervical cancer, their self-concept is often disrupted due to physical, emotional, and social changes that occur during the treatment process Objective: This study uses a systematic review approach to examine the effect of SEFT on the formation of self-concept of patients with cancer. This literature study uses search engine databases namely ProQuest, ScienceDirect, Pubmed, and Scopus, with article publications ranging from 2018 to 2024. The literature search strategy involved keywords related to the topic and title of the study, namely: "Massage" OR "foot massage" OR "reflexiology" AND "Fatigue" AND "Haemodialysis" OR "Chronic kidney disease" AND "Randomised Control" OR "Clinical Trial". 6 articles showing effective results of SEFT application in various populations. The results of this literature study show that SEFT therapy has been shown to improve the self-concept of patients with cancer. The Spiritual Emotional Freedom (SEFT) technique has shown a promising effect on cancer patients' self-concept by addressing emotional and spiritual well-being.